2021
DOI: 10.3390/app112411933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Poultry and Goat Manures on the Nutrient Content of Sesamum alatum Leafy Vegetables

Abstract: Sesamum alatum Thonn. is one of the less-popular but nutritious leafy vegetables that is still collected from the wild or as weeds among crops in South Africa. The plant is also used in medicines and cosmetics in Africa and elsewhere. Despite its importance, the cultivation of S. alatum under different agronomic systems for improved harvestable yield and nutrient content is still lacking. The study aimed to determine the response of S. alatum nutrient content to the application of poultry and goat manures. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In accordance with the statement of Wienhold and Giiley that the availability of K from manure is almost 100%, manure can be used like potassium fertilizer [19]. Goat manure is a high source of potassium when compared to other manures, such as poultry [20].…”
Section: Effect Of Bioactivators On Potassium Content In Goat Feces B...mentioning
confidence: 83%
“…In accordance with the statement of Wienhold and Giiley that the availability of K from manure is almost 100%, manure can be used like potassium fertilizer [19]. Goat manure is a high source of potassium when compared to other manures, such as poultry [20].…”
Section: Effect Of Bioactivators On Potassium Content In Goat Feces B...mentioning
confidence: 83%
“…Low nutrient use efficiencies are often the result of nutrient imbalances (Aliyu et al, 2021); indeed, visual observations in our experiments suggested that Mg, Zn and/or S were limiting in the treatments with low amounts and qualities of organic resource inputs. This was much less in the FYM treatments as manures often contain substantial amounts of micronutrients (Sileshi et al, 2019;Mbatha et al, 2021). For example, Kihara et al (2016) showed that the addition of micronutrients could significantly improve crop yields (in a range of 0.25-4 t ha -1 ) in a third of the experimental sites across multiple countries in sub-Saharan Africa.…”
Section: Yield Trends Are Site Specific So the Order Of Isfm Practice...mentioning
confidence: 99%
“…The non-signi cant difference, particularly on CCL in the current study, could probably be encouraged by signi cantly lower nitrogen levels due to ammonium (NH 3 ) volatilization, which leads to an imbalance of nutrients (Lim et The result from this study showed that DSM (6.57, 10.12, 9.17, 11.14, and 8.32 g) was accumulated in T 1 -1:31, T 2 -1:3:2, T 3 -1:3:3, T4-1:3:4, and T 5 -1:3:5 goat manure levels compared to control 6.54 g. The highest DSM reported in the current study was achieved in T 4 -11.14 g, followed by T 2 -10.12 g, T3-917 g, T5-8.32 g, and T1-6.57 g in goat manure. The high DSM growth in T4-11.14 g could be because goat manure as T 4 boosts the organic manure content to acceptable levels due to organic manure improving plant root rizoster condition (Mbatha et al 2021), thus enhancing the accumulation of nutrients from the soil. Batubara et al…”
Section: Al (2020)mentioning
confidence: 99%
“…It is still shameful that manure is not usually put on agricultural land in Sub-Saharan African (SSA) nations (Washaya and Washaya 2023). There is no literature on increasing wild watermelon yields, even though numerous studies on the use of goat manure as soil fertility have been conducted (Ansah et al 2019;Batubara et al 2021;Mbatha et al 2021;Köninger et al 2021), but very few have used. Thus, the study aimed to determine the effect of different goat manure levels on the growth yield and performance of wild watermelon (Citrullus lanatus subsp.)…”
Section: Introductionmentioning
confidence: 99%